Study of Fuel Save Controller (FSC) System in Renewable Energy: A Case Study Wangi-Wangi, Wakatobi, Indonesia - Darmana T.; Iwan Tutuka P.; Rizki Pratama P.; Suyanto H.; Rahayu S.; Hidayat R.; Abidin A.A.B.Z.; Renuga A.; Verayiah P. (Institute of Electrical and Electronics Engineers Inc., 2025)
This study evaluates the Fuel Save Controller (FSC) system's impact on Wangi-Wangi Island's renewable energy grid. Integrating solar and wind energy, the FSC system optimizes energy distribution, reduces fuel consumption, and enhances grid stability. Diesel generators currently provide 1.9 MW per hour but have high carbon emissions. Solar energy offers 0.012 MW per unit area per hour as a supplemental source, while wind energy, at 0.15 MW from 50 turbines per unit area per hour, is the primary renewable source. The FSC system saves 1.16 liters of fuel and IDR 9.89 per hour, reducing total fuel consumption to 7.88 liters per hour and costs to IDR 67.39 per hour, achieving a 14.68% reduction in both. The FSC system significantly enhances energy efficiency and sustainability, highlighting the need to transition to renewable energy sources. ? 2024 IEEE.